Process analysis of chemical looping gasification (CLG) of biomass for liquid fuel production with net-negative CO₂ emissions - Roshan Kumar, Tharun (My University, 2019)
Biomass gasification integrated with downstream Fischer-Tropsch (FT) synthesis for the production of liquid biofuel is a potential pathway to decarbonize growing transportation sectors such as aviation and maritime sectors. Chemical Looping Gasification (CLG) is a novel gasification technology that resembles indirect gasification in circulating fluidized bed, but instead of inert bed material (e.g. olivine), so-called oxygen carrier (OC), metal-oxide particles are utilized. The OC particles undergo cyclic oxidation and reduction in the air reactor and the fuel reactors, respectively, providing heat and oxygen for gasification. Thus, the raw syngas produced is more oxidized than in a conventional gasifier, with a lower concentration of tar and a higher concentration of CO2. Capturing and storage of CO2 during the subsequent gas cleaning stages would result in FT-crude production with net-negative CO2 emissions. For evaluating the performance of an integrated biomass-to-liquid (BTL) process with CLG as the primary gasification technology, an integrated process model was developed and analyzed using Aspen Plus® simulation software. The CLG process model was modelled with a thermal input of 100 MWth of waste biomass and was complemented with Fortran statements to calibrate thermodynamic equilibrium deviations, experienced during associated experimental activities or reported in the literature. LD-slag, an inexpensive and readily available by-product from steel production, was used as the primary oxygen carrier in the process models. The core gasification models were validated with experimental data from the chemical looping gasification tests done at Chalmers research boiler/gasifier with wood pellets and LD-slag as bed material. The gasification model predicts syngas composition, energy content and cold gas efficiency in good agreement with published data. Syngas with a high energy content of 12 MJ/Nm3 (LHV basis) is predicted with an average cold gas efficiency of 56.6%. A high CO2/CO ratio is also predicted in the syngas produced, which would be suitable for carbon capture. The integrated model estimates an FT-crude production of approximately 359 barrels per day with a CO2 capture capacity of 138.5 ktCO2/year. The integrated model has an average chemical efficiency, i.e. the conversion efficiency of biomass-to-FT crude of 22.8% with the chosen operating conditions. Heat integration studies show that there are adequate heat recovery possibilities for co-generation of steam and power.
Keywords: chemical looping; biomass; gasification; Fischer Tropsch Synthesis; oxygen carriers; LD-slag